2018
DOI: 10.18203/2349-3291.ijcp20183539
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of carriage of community-acquired Methicillin-resistant Staphylococcus aureus among children attending the pediatric OPD at a tertiary care hospital

Abstract: Background: Community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) infections are commonly recognized in persons without traditional risk factors. Nasal carriage of MRSA is an important risk factor for subsequent MRSA infection and transmission of this pathogen. The aim of this study was to estimate the prevalence of carriage of community acquired MRSA and to describe its antibiotic susceptibility pattern among the pediatric population.Methods: A prospective longitudinal study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The majority cases were patients that infected with wound of surgical operations, as summarized in the Table 4. Furthermore, Radhakrishnan et al 22 stated that S. aureus infections distributed between various groups of age similarly, while there were study conducted by Sdougkos et al 23 who reported that the ages between 15-60 years were high susceptible to be infected with S. aureus.…”
Section: Discussionmentioning
confidence: 99%
“…The majority cases were patients that infected with wound of surgical operations, as summarized in the Table 4. Furthermore, Radhakrishnan et al 22 stated that S. aureus infections distributed between various groups of age similarly, while there were study conducted by Sdougkos et al 23 who reported that the ages between 15-60 years were high susceptible to be infected with S. aureus.…”
Section: Discussionmentioning
confidence: 99%